Effect of Zeolite Soil Amendment on Growth, Productivity, and Economic Value of Sweet Corn (Zea mays) - Furqoni, Hafith (Fakultas Sains dan Teknologi, 2025)
Soil amendments play a vital role in enhancing soil quality. Zeolite, a commonly used amendment, is recognized for sustaining higher soil moisture. This study aimed to assess the response of sweet corn to zeolite applications through soil properties and economic analyses. A randomized complete block design (RCBD) with four replications was employed, using seven treatments: no zeolite (P0), comparative zeolite (200 kg/ha; P1), and 0.50 (100 kg/ha; P2), 0.75 (150 kg/ha; P3), 1.00 (200 kg/ha; P4), 1.25 (250 kg/ha; P5), and 1.50 (300 kg/ha; P6) of the tested dosage. Zeolite significantly improved soil pH and cation exchange capacity compared to the control. It also enhanced plant growth (height and leaf number) and yield (per plot and per hectare). Although differences among zeolite rates were not statistically significant, the 1.0 dosage offered the highest economic return and a relative agronomic effectiveness (RAE) of 263%. Thus, 200 kg/ha applied in split doses is recommended.